To evaluate post-operative shoulder tip pain in low pressure (10MMHG Co2) versus standard pressure (14MMHG Co2) pneumoperitoneum in laparoscopic cholecystectomy: A one year randomized controlled trial hospital-based study - Shaha, Anup; Shirsath, Kalpesh; Yelke, Vishal (International journal of health sciences, 2024)
Background: Nowadays, the gold standard of care for cholelithiasis is laparoscopic cholecystectomy (LC). After a LC, post-operative shoulder tip pain is a typical complaint. The main cause of this shoulder tip pain is pneumoperitoneum caused by carbon dioxide. The present study was undertaken to evaluate the post-operative shoulder tip pain in low pressure (10MMHG Co2) versus standard pressure (14MMHG Co2) pneumoperitoneum in LC. Method: A prospective randomized controlled trial incorporating 70 patients with symptomatic uncomplicated cholelithiasis who underwent LC using a four-port technique. Patients were divided randomly in two groups: 35 patients underwent Low Pressure LC (10MMHG Co2) (Group-A), and another 35 patients underwent Standard Pressure LC (14MMHG Co2) (Group-B). Postoperative shoulder tip pain was assessed at 4, 8 and 24 h after operation by the Visual Analogue Scale (VAS) of Pain. Results: 11 patients (31.42%) in group B complained of post-operative shoulder tip pain as compared to only 4 patients (11.42%) in group A which was statistically significant, (P=0.0414).